STUDY OF MAXIMUM SWIMMING SPEED BURST SPEED OF THE CORK FISH (Channa striata) - Insyani, Helmi; Zain, Jonny; ', Nofrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in August 2014, which is housed in theCapture Device Materials Laboratory, Faculty of Fisheries and ScienceKelautan.Tujuan of this study was to determine the swimming speed of fish cork.Cork fish swimming speed of normal (sustained swimming speed) is <2.9 cm / sec(less than 44.3 cm / sec), Prolonged cork fish swimming speed is 2.9 to 18.2 cm /sec (44.3 -246.1 cm / sec). Fish swimming speed burst capability cork is 18.2 cm /second (246.1 cm / sec) free swimming speed (free swimming) has positivecorrelation ie the frequency flick of the tail for second (cm / sec) it is shown at adistance of 100 cm, fish do a flick of the tail as much as 4.5 times that swim at aspeed of 100.0 (cm / sec) and at a distance of only 50cm fish tail wagging as muchas 1.5 times that swim at a speed of 12.5 (cm / sec).Keywords: endurance, swimming speed, maximum swimming speed, swimmingspeed and prolonged fish swimming freely.